(untitled) (Journal of Global Accounting, 2024)
The study examined the effect of corporate firm attributes on tax planning of listed industrial goods firms in Nigeria. The specific objective of the study is to ascertain the effect of firm leverage, firm liquidity and firm size on the book-tax difference of listed industrial goods firms in Nigeria. The study used the ex-post facto research design. The study used purposive sampling to select eight (8) out of thirteen companies that were listed in Nigeria. The study utilised secondary data collected from the financial statements of selected manufacturing firms spanning from 2013 to 2022, resulting in a historical data timeframe of 10 years. The study employed descriptive analysis to provide a detailed description of the research variables. Panel least square regression was used in testing the hypotheses. The findings showed that: firm leverage has a significant negative effect on the book-tax difference for listed industrial goods firms in Nigeria (p<0.05); firm liquidity has a non-significant negative effect on the book-tax difference for listed industrial goods firms in Nigeria (p>0.05); firm size has a non-significant negative effect on the book-tax difference for listed industrial goods firms in Nigeria (p>0.05). The study recommends that managers of industrial goods firms in Nigeria should optimize tax planning strategies by leveraging increased debt financing, strategically structuring financial operations to capitalize on interest deductions and minimize overall tax liabilities for listed industrial goods firms in Nigeria